Manufacturing of Microfibrillated Cellulose from Never-Dried Microcrystalline Cellulose Using Masuko Grinder - Annina Lähdeniemi; Aaro Knuts; Olli Dahl (BioResources, 2024)
Microfibrillated cellulose (MFC) batches were produced using never-dried and commercial, dried microcrystalline cellulose (MCC) as raw materials. Mechanical treatment was applied with a Masuko grinder using different refining degrees and consisting of one to three passes through the equipment. The impact of the mechanical treatment on the particle size distribution, fiber swelling properties, particle morphology as well as rheology of the manufactured MFC gel products were investigated. In addition, specific energy consumption of the process was calculated. The MFC gel samples manufactured from the never-dried AaltoCell™ MCC, demonstrated more pronounced changes in material properties with various refining parameters than those produced from the commercial, dried MCC, which is likely attributable to the hornification effect. The most significant reduction in particle sizes and the greatest increase in fiber saturation point and rheological properties were achieved during the initial pass through the grinder. The use of never-dried MCC as the raw material resulted in a stronger MFC gel with higher storage and loss modulus characteristics. Specific energy consumption also indicated that the refining energy transfers better to the never-dried structure of MCC, and more fibrillation can be obtained with less energy when using the never-dried MCC as raw material for MFC production.